Survey Of Prescription Pattern Of Anti-Hypertensive Drugs In Hypertensives And Hypertension Associated Diabetics - TASNEEM SANDOZI; VAMSI KRISHNA EMANI (International Journal of Pharma and Bio Sciences, 2010)
To evaluate drug utilization in hypertensives and diabetic hypertensives in a tertiary care Princess Esra Hospital, Hyderabad, India. This was a cross-sectional study done in the outpatient department of Internal Medicine at Princess Esra Hospital, Hyderabad. It was done in 2 phases between 2008 and 2009-10. 300 patients were studied in 2008 (phase I) and 450 patients were studied in 2009-10 (phase 2). In phase 1, 59% of patients were on mono-drug therapy whereas in phase 2, 72% of patients were on mono-drug therapy. Calcium channel blockers (CCBs) (35.59%) were most commonly used in phase 1 whereas in phase 2, angiotensin converting enzyme inhibitors (ACEIs) (47.24%) were most commonly used. In phase 1 – 41% were on combinations and the combination of ACEIs and diuretics (29.27%) was most commonly prescribed. In phase 2 – 28% were on combinations and the combination of beta-blockers and CCBs (28.58%) was most commonly prescribed. 189 diabetic hypertensive prescriptions were evaluated (84 in phase 1 and 105 in phase 2). 50% of these patients were on ACEIs and 28.58% were on combination therapy of ACEIs and diuretics. In this study , when compared to phase 1 there is a drastic increase in usage of ACEIs in phase 2 as mono-drug regimen and a significant decline in usage of beta-blockers in mono-drug regimen. In combinations, usage of CCBs and beta blockers increased. In diabetic hypertensives the use of ACEIs and angiotensin receptor blockers (ARBs) alone or in combination were prescribed to nearly 80% of patients.